Heavy drinking among individuals with HIV: who drinks despite knowledge of the risk?. Issue 5 (4th May 2018) - Elliott, Jennifer C.; Stohl, Malka; Hasin, Deborah S.
ABSTRACT: Heavy drinking can cause medical problems for individuals with HIV, and drinking despite medical contraindications indicates problem use. However, little is known about which individuals with HIV drink despite knowledge of health problems. This study utilizes two subsamples of individuals with HIV from the National Epidemiologic Survey on Alcohol and Related Conditions-III (NESARC-III): those reporting at least one drink (a) in their lifetime ( n = 205) or (b) in the past year ( n = 166). Participants reported on drinking despite health problems and psychopathology in the past year and in their lifetime, and family history of alcohol problems. Individuals with a drug use disorder (Adjusted Odds Ratios [AORs] = 3.56–12.65), major depressive disorder (AORs = 10.18–10.55), or a family history of alcohol problems (AORs = 33.60–96.01) were more likely to drink despite health problems. Anxiety and personality disorders did not increase risk. Individuals with HIV with drug use disorders or major depressive disorder are more likely to drink despite health problems. Individuals with a family history of alcohol problems were also more likely to do so, although further research is needed given large confidence intervals. Future research should consider how to help these individuals avoid alcohol-related harm.